2022
DOI: 10.3389/fpubh.2022.931557
|View full text |Cite
|
Sign up to set email alerts
|

How health motivation moderates the effect of intention and usage of wearable medical devices? An empirical study in Malaysia

Abstract: Mobile technology is popular because it facilitates users in multiple ways. This technology is revolutionising the healthcare industry, and mobile-based wearable medical devices (WMDs) are becoming common. Technology adoption is always challenging, and technology value is based on the technology attributes and personal inclination towards using the technology. This study investigates how the perceived product value is influenced by compatibility, cost, personal privacy, technology accuracy, and usefulness. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…It is also suggested that PLS-SEM should be applied when developing an initial theory for exploratory research models. So, Smart-PLS software, one of the well-known software applications for PLS-SEM, was used to analyze the data ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also suggested that PLS-SEM should be applied when developing an initial theory for exploratory research models. So, Smart-PLS software, one of the well-known software applications for PLS-SEM, was used to analyze the data ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al ( 21 ) explored and demonstrated the intention and adoption of Wearable Fitness Devices among Chinese adults. Hayat et al ( 22 ) investigated that the perceived product value instigates the intention to use wearable medical devices and health motivation, and the intention to use promotes the adoption of wearable medical devices.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 1 , 34 Consumers are expected to possess information before they can understand the benefits and values acquired from using a product or service, which might then influence their behavioral intention. 17 Users are enticed to buy fitness equipment because of the health information and benefits they can attain from the equipment. 1 , 19 A user will be satisfied if the wearable technology device, which includes a fitness tracker, surpasses the desirable health improvement.…”
Section: Literature Assessmentmentioning
confidence: 99%
“… 2 Given these difficulties and uncertainties during COVID-19, it is probable that interest in healthcare devices and apps will continue to grow in the future. 17 More individuals have become interested in their health and physical and psychological well-being due to the COVID-19 pandemic; they desire to deliver exercises and fitness content to their homes via WFDs. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Health motivation is a type of motivation for physical exercise whereby individuals are motivated to exercise for health purposes. Individuals motivated by health are more likely to accept and participate in health-related interventions ( 11 ). Because people focused on health during the epidemic, health motivation may be a moderator of the mental stress buffer effect of physical exercise in this setting.…”
Section: Literature Reviewmentioning
confidence: 99%